2015
DOI: 10.1103/physrevlett.115.044302
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-Layer Effects on Acoustic Transmission Through Narrow Slit Cavities

Abstract: We explore the slit-width dependence of the resonant transmission of sound in air through both a slit array formed of aluminum slats and a single open-ended slit cavity in an aluminum plate. Our experimental results accord well with Lord Rayleigh's theory concerning how thin viscous and thermal boundary layers at a slit's walls affect the acoustic wave across the whole slit cavity. By measuring accurately the frequencies of the Fabry-Perot-like cavity resonances, we find a significant 5% reduction in the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 20 publications
2
92
0
Order By: Relevance
“…The space-coiling design has not yet been demonstrated in water, where common solids such as steel that might be used to confine the coils cannot be assumed to be perfectly rigid due to their significantly smaller density contrast with water-thus introducing the challenge of elastic coupling [37] that must be incorporated into any design strategy. Although the kinematic viscosity of water is less than that of air [23], recent measurements of air-borne space-coiled metamaterials [36] demonstrate significant attenuation, and we caution that viscous effects should not be neglected in aqueous designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The space-coiling design has not yet been demonstrated in water, where common solids such as steel that might be used to confine the coils cannot be assumed to be perfectly rigid due to their significantly smaller density contrast with water-thus introducing the challenge of elastic coupling [37] that must be incorporated into any design strategy. Although the kinematic viscosity of water is less than that of air [23], recent measurements of air-borne space-coiled metamaterials [36] demonstrate significant attenuation, and we caution that viscous effects should not be neglected in aqueous designs.…”
Section: Discussionmentioning
confidence: 99%
“…For our measurement temperature of 293 K and the lowest operational frequency of 5 kHz, the viscous and thermal boundary layers in water are calculated to be 8 and 3 μm, respectively. These boundary layers are less than 0.3% of the smallest cylinder separation in our lattice, a value that is much lower than the approximately 5% threshold that was recently demonstrated to impact acoustic performance in small channels [23]. The impact of viscosity and heating is also derived for sonic crystal lattices composed of rigid [24] and elastic [25] scatterers, and the application of this theory to our lattice geometry under a rigid approximation results in a negligible dissipation factor of one part in a thousand.…”
Section: Methodsmentioning
confidence: 99%
“…These values are less than 2% of the minimum separation, d, between building units in the metamaterial lattice; d ¼ 2R ext − a. This value is lower than the approximately 5% threshold that was recently demonstrated to impact acoustic performance in small channels [36]. Regarding the separation between walls inside a building unit, the minimum distance is given by 2πR a =16.…”
Section: Scaling Of the Metamaterialsmentioning
confidence: 99%
“…When dealing with such subwavelength structures, it was notably showed that dissipation due to boundary layer effects cannot be neglected [37]. In our numerical calculation of transmission spectrum, represented in Figure 6, we have included thermoacoustic equations in order to take into account dissipations.…”
mentioning
confidence: 99%